Epidemiology of multiple congenital anomalies in Europe: A EUROCAT population‐based registry study. Issue 4 (11th April 2014) - Calzolari, Elisa; Barisic, Ingeborg; Loane, Maria; Morris, Joan; Wellesley, Diana; Dolk, Helen; Addor, Marie‐Claude; Arriola, Larraitz; Bianchi, Fabrizio; Neville, Amanda J.; Budd, Judith L.S.; Klungsoyr, Kari; et al.
Abstract : Background: This study describes the prevalence, associated anomalies, and demographic characteristics of cases of multiple congenital anomalies (MCA) in 19 population‐based European registries (EUROCAT) covering 959, 446 births in 2004 and 2010. Methods: EUROCAT implemented a computer algorithm for classification of congenital anomaly cases followed by manual review of potential MCA cases by geneticists. MCA cases are defined as cases with two or more major anomalies of different organ systems, excluding sequences, chromosomal and monogenic syndromes. Results: The combination of an epidemiological and clinical approach for classification of cases has improved the quality and accuracy of the MCA data. Total prevalence of MCA cases was 15.8 per 10, 000 births. Fetal deaths and termination of pregnancy were significantly more frequent in MCA cases compared with isolated cases ( p  < 0.001) and MCA cases were more frequently prenatally diagnosed ( p  < 0.001). Live born infants with MCA were more often born preterm ( p  < 0.01) and with birth weight < 2500 grams ( p  < 0.01). Respiratory and ear, face, and neck anomalies were the most likely to occur with other anomalies (34% and 32%) and congenital heart defects and limb anomalies were the least likely to occur with other anomalies (13%) ( p  < 0.01). However, due to their high prevalence, congenital heart defects were present in half of all MCA cases. Among males with MCA, the frequency of genital anomalies was significantly greater than the frequency of genital anomalies among females with MCA ( p  < 0.001). Conclusion: Although rare, MCA cases are an important public health issue, because of their severity. The EUROCAT database of MCA cases will allow future investigation on the epidemiology of these conditions and related clinical and diagnostic problems. Birth Defects Research (Part A) 100:270–276, 2014. © 2014 Wiley Periodicals, Inc.